Persepsi Dai Tentang Keberadaan Allah (Studi Pada Majelis Taklim As-Sakinah Di Kota Pematangsiantar) - Suhendri hamzah; Muhammad Fadhil Azman (Bashirah, 2022)
This study aims to determine how the dai's perception of the existence of Allah in the Taklim as-Sakinah Council is. This type of research is descriptive qualitative, namely the procedure that produces descriptive data in the form of written or spoken words from the people being observed. This approach was carried out to find out the dai's perception of the existence of Allah at the as-Sakinah takllim assembly. While the research specification here is descriptive qualitative which is trying to describe the situation with a particular event or activity. Data collection techniques that researchers use include interviews. The technique that the researcher uses is qualitative data analysis. The result of this study is that the preachers at the as-Sakinah taklim assembly chose a different perception of the existence of Allah, but what dominates is the perception of those who say that Allah is everywhere.